Flow control of a stalled S809 airfoil using an oscillating micro-cylinder at different angles of attack. (September 2021) - Shi, Xuyang; Sun, Jinjing; Zhong, Shan; Huang, Diangui
Abstract: The flow control effects on the S809 airfoil produced by an oscillating micro-cylinder placed upstream of the airfoil suction surface were investigated using numerical simulations at Reynold number of 1 × 10 6 and high angles of attack ( α ) range from 20° to 24°. The oscillating mode and initial position of the micro-cylinder are two main parameters considered in this paper. The numerical results suggest that at the start of a heavy stall angle of attack ( α  < 22°), flow separation can be suppressed when the optimum oscillating mode and initial position of the micro-cylinder were given. However, once the airfoil is confronted to heavy stall angles of attack ( α  > 22°), its aerodynamic performance could only be lightly improved or even deteriorated because of the strong and large adverse separation which could not be controlled effectively by the small oscillating cylinder. It was also found that a better control effect can be obtained when the initial position of the cylinder was set adjacent to the separation point compared with that placed near the leading edge at α  = 21°. Furthermore, our results also showed that higher dimensionless oscillating amplitudes and a larger frequency can obtain a higher lift-to-drag ratio when the micro-cylinder was placed at optimal initial position. Highlights: New flow control method using an oscillating micro-cylinder was investigated. This flow control method is easy to implement and has important practical application. With proper setting, oscillating micro-cylinder has good effect at different angles of attack. The oscillating mode of micro-cylinder will impact the control effect. The initial position of the cylinder has significant impact on control effect.